O lugar político do filósofo : estudo sobre a atopía no Górgias de Platão - George Matias de Almeida Júnior (2012)
According to tradition, Plato laid down the basis for the philosophical paradox of the relationship between philosophy and the polis, putting forth the question whether the philosopher belongs to the city or is absent from its practices. Our thesis questions this vital topos in socratic and platonic studies and throws new light on a problem that is nuclear to western political philosophy, by analyzing the political role of the philosopher in Plato´s Gorgias. Against the conventional labels according to which Plato´s political philosophy is utopic, authoritarian and anti-democratic, we argue that the political dimension is as effective as it is decisive for a correct understanding of all of his writings, no matter how strange, eccentric and out of place it may be. We propose to renew this topos by focusing on this unique and paradigmatic dialogue, insofar as it represents, not a transitional moment in Plato´s philosophy, but an autonomous and acute reflection on the political place of the philosopher as atopia, or a non-place. Such idea is presented and discussed in its threefold conceptual dimension of strangeness, contradiction and displacement, which is meant to help us understand it, not explain it away. Thus, by arguing that the philosopher´s atopia is his only and genuine topos we show how this oxymoron should make perfect sense to the attentive reader, due to the ambiguous and out of ordinary character of Plato´s political philosophy, which we sustain by giving special emphasis to the notion of philosophy as the best way of living.